2002
DOI: 10.1046/j.1365-201x.2002.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate and intensive training on the hypothalamo–pituitary–adrenal axis in rats

Abstract: The influence of the two distinct training programmes, moderate (M) and intensive (I), on hypothalamo-pituitary-adrenal (HPA) axis was investigated, in rats. Changes in plasma concentrations of adrenocorticotropin hormone (ACTH) and corticosterone were followed in response to (i) a 60-min acute running session performed on 2nd, 4th and 6th of the seven training weeks (ii) an acute restraint stress of 40 min applied after the final training programme. After 2nd, 4th and 6th week of the two training programmes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
5
37
1
1
Order By: Relevance
“…These results corroborate the literature with trained rats on treadmill under high intensity protocols, which reduce the food intake with consequent weight loss (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) . As mentioned before and reinforcing such idea, physical exercises represent a type of stress and promote CRH release by the hypothalamus due to the dependence of the stressor agent intensity.…”
Section: Esupporting
confidence: 81%
See 2 more Smart Citations
“…These results corroborate the literature with trained rats on treadmill under high intensity protocols, which reduce the food intake with consequent weight loss (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) . As mentioned before and reinforcing such idea, physical exercises represent a type of stress and promote CRH release by the hypothalamus due to the dependence of the stressor agent intensity.…”
Section: Esupporting
confidence: 81%
“…Actually, Oliveira et al (54) reported that the primary function of the kidneys is to regulate the volume and composition of the extra cellular liquid, and hence, these alterations that occur during the performance of physical exercises may generate hemodynamic changes and changes in the sodium and water excretion. The findings of this study concerning the kidneys weight of the trained animals do not confirm the findings of the literature (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) , showing decrease in this organ's weight, maybe by the decrease of the number of glomerulus caused by the hypoxia conditions imposed by the exercises. One of the possible causes of this results divergence may be the fact that the research was performed with rats too young for the physical training, differently from the age of the rats from this study.…”
Section: Econtrasting
confidence: 54%
See 1 more Smart Citation
“…The effects of regular exercise on diurnal GC levels and adrenal sensitivity to ACTH secretion are unclear. Previously, a number of rodent studies investigating the effects of training on the HPA axis have employed forced exercise paradigms for their method of training (1,25,27,36). Such studies have produced findings that are similar to those of investigations employing chronic stress (e.g., repeated restraint stress) as an activator of the axis (17,32), making it difficult to delineate the effects of perceived stress from the exercise itself.…”
mentioning
confidence: 82%
“…For example, forced treadmill running, water immersion and so on. 10,11 are perceived as psychological stress, 12 which may complicate interpretation of results. A preferred method is the use of running wheels in which rodents can run voluntarily.…”
Section: Introductionmentioning
confidence: 99%